Threshold for blowup for equivariant wave maps in higher dimensions. (7th March 2017) - Biernat, Paweł; Bizoń, Piotr; Maliborski, Maciej
Abstract: We consider equivariant wave maps from R d + 1 to S d in supercritical dimensions 3 ⩽ d ⩽ 6 . Using mixed numerical and analytic methods, we show that the threshold of blowup is given by the codimension-one stable manifold of a self-similar solution with one instability. To probe self-similar blowup, we develop a novel numerical method, based on an adaptive rescaling of coordinates, which may be of independent interest in numerical studies of singularity formation.